A High-salt diet induces renal dysfunction and alters cardiometabolic homeostasis through elevation of circulating renal dysfunctionlevels in Wistar rats. - Ligan, J.C.K.; MEDEHOUENOU, THIERRY COMLAN MARC; Segbo, A.G.J.; Akpovi, D. Casimir (My University, 2022)
There is increasing evidence in support of a decisive role played by the diet in the development of non-communicable diseases. The present study aimed to assess the effect of salt overfeeding on renal function and on the cardiovascular system in Wistar rats. Four groups of rats were exposed to diets with various salt levels, 0.8% for control, and 2%, 4% and 8% for overfed rats during 12 weeks. Blood Glucose, Triglycerides, Total cholesterol, LDL cholesterol (LDL-c) and HDL cholesterol (HDL-c) levels were determined by enzymatic method and serum PCSK9 by ELISA. Kidneys’ histology sections were treated with hematoxylin-eosin staining. Serum creatinine (17.54±2.35 mg/L vs. 11.06±0.95 mg/L; p<0.05) and urea (1.48±0.37 g/L vs. 0.48±0.04 g/L; p<0.05) were significantly increased in overfed rats compared to control. Structural alteration of glomeruli and extensive tubular lesions were observed in rats fed with 4% and 8% salt. High salt intake caused a significant increase in Na+ (171.9±2.1 mEq/L vs. 148.4±2.6 mEq/L; p<0.01), K+ (8.3±0.4 mEq/L vs. 7.2±0.1 mEq/L; p<0.05), and Cl- (109.9±5.1 mEq/L vs. 96.0±1.6 mEq/L; p <0.01) levels at week 12 compared to control. Triglycerides (1.49±0.31 g/L vs. 0.89±0.05 g/L; p <0.05), LDL-c (0.59±0.09 g/L vs. 0.31±0.03 g/L; p <0,05) and serum PCSK9 (10.28±3.21 ng/ml vs. 0.98±0.11 g/L; p <0.001) were significantly increased in salt overfed rats compared to control. Our results suggest that high salt intake impairs renal morphology and function and increases the risks of cardiovascular disease through circulating PCSK9 level increasing.
Keywords: renal dysfunction; Wistar rats